2009
DOI: 10.1097/mbc.0b013e32832e0618
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pitavastatin on monocyte chemoattractant protein-1 in hyperlipidemic patients

Abstract: The effects of statins on platelet activation markers, chemokines and adiponectin, were investigated in 135 patients with hyperlipidemia. Of the 135 hyperlipidemic patients, 63 were allocated to the simvastatin group, treated with simvastatin at the dose of 10 mg daily, and the remaining 72 were allocated to the pitavastatin group, treated with pitavastatin at the dose of 2 mg daily. Plasma levels of platelet-derived microparticles (PDMP), cell adhesion molecules (sCD40L and sP-selectin), chemokines [monocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…Adiponectin increased in response to pitavastatin but not in response to simvastatin [74] Humans with increased cardiovascular risk 12 wk of 10-80 mg/d atorvastatin Adiponectin increased by 10% with maximal increase (25%) observed at 80 mg/d (P < 0.05) [75] Humans with hypercholesterolemia and CAD b 6 mo of 10-20 mg/d pravastatin Adiponectin increased by 16.8% from 7.2 to 7.8 µg/mL (P < 0.001) [76] Humans with hypercholesterolemia and ischemic heart disease 3 mo of 10 mg/d atorvastatin Adiponectin increased from 9.7 ± 7.4 to 13.9 ± 9.98 µg/mL (P < 0.005) [77] C57BL/6J mice 0-15 wk of 0.06% of diet as pravastatin…”
Section: Leptinmentioning
confidence: 90%
See 4 more Smart Citations
“…Adiponectin increased in response to pitavastatin but not in response to simvastatin [74] Humans with increased cardiovascular risk 12 wk of 10-80 mg/d atorvastatin Adiponectin increased by 10% with maximal increase (25%) observed at 80 mg/d (P < 0.05) [75] Humans with hypercholesterolemia and CAD b 6 mo of 10-20 mg/d pravastatin Adiponectin increased by 16.8% from 7.2 to 7.8 µg/mL (P < 0.001) [76] Humans with hypercholesterolemia and ischemic heart disease 3 mo of 10 mg/d atorvastatin Adiponectin increased from 9.7 ± 7.4 to 13.9 ± 9.98 µg/mL (P < 0.005) [77] C57BL/6J mice 0-15 wk of 0.06% of diet as pravastatin…”
Section: Leptinmentioning
confidence: 90%
“…Indeed, atorvastatin increased plasma adiponectin levels in men with hypercholesterolemia and increased adiponectin production and secretion in 3T3-L1 adipocytes [78] . Conversely, other studies examining the effects of simvastatin demonstrated that adiponectin concentrations were either unchanged [74,81] or reduced [82][83][84][85] . Nomura and colleagues tested the effects of either pitavastatin or simvastatin in humans with hypercholesterolemia and found that plasma total adiponectin concentrations increased after six months of pitavastatin treatment, but were unaffected by simvastatin [74] .…”
Section: Adiponectinmentioning
confidence: 91%
See 3 more Smart Citations